Spatial dataset on future forest cover changes in Southeast Asia projected under the shared socioeconomic pathways - Ronald C. Estoque (Data in Brief, 2023)
The five shared socioeconomic pathways (SSPs) provide future projections for various social-ecological variables, including forest cover. However, these projections are limited to quantities and lack a spatial dimension. This dataset is the result of an effort to spatialize the projected forest cover changes (losses and gains) (2015-2050) in Southeast Asia under the five baseline SSPs. The dataset is available in GIS raster format (.tif) at a spatial resolution of 300 m. A wide range of users can benefit from this dataset, as it can be used independently or in conjunction with other datasets. Specifically, it can be employed to assess potential future social-ecological impacts, both positive and negative, in Southeast Asia resulting from changes in forest cover. The dataset supports analysis at the national, sub-national, or landscape levels.